ANIMAL WELFARE IN BEEF CATTLE PRODUCTION: a bibliographic review - Tamires Lotti, Juliana; Ferrarezi Junior, Edemar (Revista Interface Tecnológica, 2023)
The study analyzes the importance of incorporating welfare together with livestock in animal production systems and in obtaining the final result, which, in this context, is beef. This analysis is based on bibliographic reviews covering sources such as websites, books, articles and monographs. The objective is to base the discussion on the subject, which arises from the concern with the handling conditions throughout the process, from the origin of the animals to their arrival at the slaughterhouses. This focus is intrinsically connected to all participants in the production chain and reflects the joint effort to achieve high quality and safe products, produced in a sustainable and ethical manner. The lack of prioritization of animal welfare in management practices results in the exposure of animals to harmful levels of stress, causing negative consequences in all stages of the production chain. The central purpose of this research was to conduct a comprehensive assessment of animal welfare principles, with a special focus on their application to beef cattle. This focus aims to understand how animal welfare directly influences the quality of the final product.